High-nitrate vegetable diet increases plasma nitrate and nitrite concentrations and reduces blood pressure in healthy women - Ashworth, Ann; Mitchell, Klaus; Blackwell, Jamie R; Vanhatalo, Anni; Jones, Andrew M (Public health nutrition, 2015)
Epidemiological studies suggest that green leafy vegetables, which are high in dietary nitrate, are protective against CVD such as stroke. High blood pressure (BP) is a major risk factor for stroke and inorganic nitrate has been shown to reduce BP. The objective of the present study was to test the hypothesis that diets containing high-nitrate (HN) vegetables would increase plasma nitrate and nitrite concentrations and reduce BP in healthy women. A randomized, crossover trial, where participants received HN vegetables (HN diet) or avoided HN vegetables (Control diet) for 1 week. Before and after each intervention, resting BP and plasma nitrate and nitrite concentrations were measured. University of Exeter, UK. Nineteen healthy women (mean age 20 (sd 2) years; mean BMI 22·5 (sd 3·8) kg/m2). The HN diet significantly increased plasma nitrate concentration (before HN diet: mean 24·4 (sd 5·6) µmol/l; after HN diet: mean 61·0 (sd 44·1) µmol/l, P<0·05) and plasma nitrite concentration (before HN diet: mean 98 (sd 91) nmol/l; after HN diet: mean 185 (sd 34) nmol/l, P<0·05). No significant change in plasma nitrate or nitrite concentration was observed after the Control diet. The HN diet significantly reduced resting systolic BP (before HN diet: mean 107 (sd 9) mmHg; after HN diet: mean 103 (sd 6) mmHg, P<0·05). No significant change in systolic BP was observed after the Control diet (before Control diet: mean 106 (sd 8) mmHg; after Control diet: mean 106 (sd 8) mmHg). Consumption of HN vegetables significantly increased plasma nitrate and nitrite concentrations and reduced BP in normotensive women.